The comparison of municipality recyclable waste collection performances with fuzzy based integrated approaches - (:unkn) unknown (Computers and Industrial Engineering, 2014)
It is important to evaluate the performance of the organizations to provide an effective management. However, a more crucial point is to determine the position among the competitors via a performance evaluation system. This system is mainly based on specific performance criteria. Therefore, the performance criteria have to be determined attentively. In addition to this, selecting the proper tool which will utilize these criteria is also essential. Within this study, it is mainly focused on the development of performance evaluation systems in municipalities regarding their waste collection system, specifically recyclable material collection system. The key performance indicators are determined by analyzing the related literature and practical applications. Moreover, as a performance evaluation tool, two integrated approaches; fuzzy AHP based TOPSIS and fuzzy AHP based VIKOR are used. Firstly, the relative importance weights of criteria are assessed by fuzzy AHP and then these values are used as an input in the two most prevalent decision making techniques TOPSIS and VIKOR, separately. The proposed integrated approaches are performed for the town municipalities in Istanbul.
Keywords: Fuzzy AHP; Municipality; Performance measurement; Topsis; Vikor